PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR IPS KELAS V SEKOLAH DASAR NEGERI 26 PONTIANAK - Aprianti, Paskalia; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problems in this study are: â€œIs there any influence of the Scientific approach on the learning outcomes of Social Sciences in fifth grade students of elementary school 26 Pontianak?; How big the influence of the Scientific approach on the learning outcomes of Social Sciences in fifth grade student of elementary school 26 Pontianak?â€. The method used is an experimental method with a quasi-experimental design. The population in this study were students of VA and VB classes at elementary school 26 Pontianak. The data collected uses measurement techniques in form of multiple choice tests. The result of the study showed that the post-test of control class 67.23 and the experimental class 75.91. According to the t-test, the significance = 3.2656 > 1.997, it means that there is an influence of Scientific approach on the learning outcomes of Social Sciences in fifth grade students of elementary school 26 Pontianak. The result of the calculation of the effect size of 0.87 means that learning using the Scientific approach has a major effect on the learning outcomes of Social Science on fifth grade students at elementary school 26 Pontianak.Â Â  Keywords: Influence, Learning Outcomes,Â  Scientific Approach, Social Sciences